Moscow and the Italian Communist Party : from Togliatti to Berlinguer - Urban, Joan Barth (London : Tauris, 1986)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Partito Comunista Italiano (PCI).; Italië